Rancang Bangun Robot Terbang Penghindar Halangan dalam Ruangan Bersekat - ., Sugianto Kusuma Indrawan (Jurnal Teknik Elektro Universitas Tanjungpura, 2018)
Technological developments in the world of robotics later lead to flying robots. One type of flying robot or Unmanned Aerial Vehicle (UAV) is a quadcopter. In this study, researchers designed a quadcopter for navigation needs in a room that is capable of automatically avoiding obstacles (obstacle avoidance). Quadcopter design in this study uses four SRF-05 ultrasonic sensors mounted on the sides of the quadcopter. Effective distance of ultrasonic sensor readings used between 3 cm - 3 m. The sensor can only work well in that range. If the distance between the sensor and the barrier wall is outside the range of values, the sensor cannot detect the barrier wall properly so that an error will occur in reading the value.Â Keywords: UAV, quadcopter, obstacle avoidance, SRF-05 ultrasonic sensor